Mengembangkan Nilai Gotong Royong pada Anak Kelompok B dengan Metode Berbasis Proyek Melalui Kegiatan Berkebun di Raudhatul Athfal Yabus (Desa Keude Krueng Geukuh, Kecamatan Dewantara) - Jufri, Jufri; Nalatirrizqa, Nalatirrizqa; Yusra, Yusra (Medan Resource Center, 2025)
This study investigates the development of mutual cooperation values among BI group children at RA Yabus through a project-based learning method centered on gardening activities. The background of the research highlights the lack of significant growth in cooperative behavior, attributed to the conventional use of group-based learning by teachers. The central research question explores how project-based methods can foster mutual cooperation in early childhood education. Employing a qualitative approach with classroom action research (CAR) design, data were collected through observation, interviews, and documentation, and analyzed using descriptive qualitative techniques. The findings indicate a marked improvement in mutual cooperation values among the children. In the pre-research and first cycle, 1% of children were at the 'not yet developing' (BB) stage, while 99% were at the 'beginning to develop' (MB) stage, with no children reaching the 'expected development' (BSH) or 'very well developed' (BSB) levels. By the second cycle, outcomes significantly shifted, with 20% reaching BSH and 80% achieving BSB. These results demonstrate that project-based methods, particularly gardening activities, effectively cultivate the value of mutual cooperation in early childhood settings.